Storytelling as a Method of Early Childhood Faith Formation: A Christian Educational Perspective - Nindo Septian Sibarani (Global Education Journal, 2026)
Faith formation during early childhood constitutes a critical foundation for lifelong spiritual development. Nevertheless, Christian religious education frequently relies on teacher-centered instruction that emphasizes cognitive knowledge over meaningful spiritual engagement. This article examines storytelling as a transformative pedagogical method for fostering faith formation in young children from a Christian educational perspective. Employing a qualitative library research approach, the study synthesizes biblical, theological, educational, and developmental literature to construct a conceptual framework for faith-based storytelling. The analysis demonstrates that storytelling is deeply rooted in the biblical tradition, where narratives function as primary instruments for transmitting faith across generations, as reflected in Deuteronomy 6:4–9, Psalm 78:1–8, and the teaching ministry of Jesus. Furthermore, storytelling aligns with children's cognitive, emotional, and moral development by stimulating imagination, nurturing empathy, strengthening memory, and facilitating personal engagement with biblical truths. Building on these findings, the article proposes a Christian Faith Storytelling Model comprising five interconnected stages: Encounter, Narrative, Reflection, Faith Response, and Habit Formation. This model provides an integrative pedagogical framework that connects biblical narratives with children's lived experiences, enabling the internalization of Christian values and the cultivation of spiritual identity. The study concludes that storytelling is not merely an instructional technique but a transformative pedagogical practice that significantly contributes to holistic faith formation in early childhood within Christian educational contexts.